Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-79232-1_6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of VoIP Quality over WiBro

Abstract: Abstract. In this work, we have conducted experiments to evaluate QoS of VoIP applications over the WiBro network. In order to capture the baseline performance of the WiBro network we measure and analyze the characteristics of delay and throughput under stationary and mobile scenarios. Then we evaluate QoS of VoIP applications using the E-Model of ITU-T G.107. Our measurements show that the achievable maximum throughputs are 5.3 Mbps in downlink and 2 Mbps in uplink. VoIP quality is better than or at least as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Their result shows that TCP throughput on HSDPA is around 1 Mbps and that on WCDMA is 350 Kbps; both are close to corresponding ISPs advertised limits. Han et al measured UDP throughput and VoIP quality over an WiBro network in a subway [6]. The UDP throughput is stable around 5.3 Mbps for downlink and 2 Mbps for uplink even in the subway moving at speed over 90 km/h.…”
Section: Related Workmentioning
confidence: 99%
“…Their result shows that TCP throughput on HSDPA is around 1 Mbps and that on WCDMA is 350 Kbps; both are close to corresponding ISPs advertised limits. Han et al measured UDP throughput and VoIP quality over an WiBro network in a subway [6]. The UDP throughput is stable around 5.3 Mbps for downlink and 2 Mbps for uplink even in the subway moving at speed over 90 km/h.…”
Section: Related Workmentioning
confidence: 99%
“…In our previous work, we analyzed the throughput and delay performance of WiBro system in various environments [5]. Similarly, QoS of VoIP applications is evaluate based on the measured throughput, delay and packet losses in [6]. It was shown that the round trip time (RTT) delay performance of WiBro system is poor compared with the conventional data networks, e.g., Ethernet or Wi-Fi networks, though the throughput performance is quite good.…”
Section: Introduction Wibro (Wireless Broadband) Is a Korean Versimentioning
confidence: 99%
“…More recent studies used mobile WiMAX networks and assessed the performance of wireless Internet applications including BitTorrent [32], World of Warcraft [33], TCP and UDP [34], TCP [35], and VoIP [36] [37].…”
Section: Related Workmentioning
confidence: 99%